2014
DOI: 10.1364/ol.39.002210
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic diffractive microscopy of living cells based on a common-path configuration

Abstract: We demonstrate a common-path tomographic diffractive microscopy technique for three-dimensional (3D) refractive-index (RI) imaging of unstained living cells. A diffraction grating is utilized to generate a reference beam that traverses a blank region of the sample in a common-path off-axis interferometry setup. Single-shot phase images captured at multiple illumination angles are used for 3D RI reconstruction based on optical diffraction tomography. The common-path configuration shows lower temporal phase fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…All phase projections were then processed digitally to create the 3D refractive‐index map of the cell by both the filtered back projection and the diffraction‐theory reconstruction algorithms 13, 30. In this reconstruction process, each projection is mapped to a surface in the 3D Fourier space, where the full rotation provided by DEP enables a full angular coverage of the Fourier space, in contrast to previous methods possessing limited angular range1, 2, 3, 4, 5, 6, 7 (see comparison in Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All phase projections were then processed digitally to create the 3D refractive‐index map of the cell by both the filtered back projection and the diffraction‐theory reconstruction algorithms 13, 30. In this reconstruction process, each projection is mapped to a surface in the 3D Fourier space, where the full rotation provided by DEP enables a full angular coverage of the Fourier space, in contrast to previous methods possessing limited angular range1, 2, 3, 4, 5, 6, 7 (see comparison in Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…To view the sample from multiple angles, one can rotate the illumination beam, while leaving the measured specimen stationary 1, 2, 3, 4, 5, 6, 7. This approach is noninvasive to the sample during data acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Refractive-index detection offers techniques to noninvasively probe the structural and chemical information of biological cells including their morphology, dynamics and concentration of specific substances [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous approaches measured the transmitted field from multiple angles, as implemented by either illumination beam rotation [4][5][6][7][8] or sample rotation [2][3]9]. The main concept of the first method is to rotate the illumination beam, while the specimen and optical setup are fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ODT has been widely used to study various biological samples including red blood cells [15][16][17][18][19][20][21][22] , white blood cells (WBC) 23,24 , hepatocytes 25 , cancer cells 16,[26][27][28][29][30][31][32] , neurons 32,33 , bacteria 34,35 , phytoplankton 36 , and hair 37 . In our previous study, we reported that ODT enables the quantitative analysis of WBCs including lymphocytes and macrophages 23 .…”
mentioning
confidence: 99%